Non-invasive tests for the diagnosis of helicobacter pylori: state of the art - Kayali, Stefano; Aloe, Rosalia; Bonaguri, Chiara; Gaiani, Federica; Manfredi, Marco; Leandro, Gioacchino; Fornaroli, Fabiola; Di Mario, Francesco; de' Angelis, Gian Luigi (Acta Biomedica Atenei Parmensis, 2018)
Usually, non-invasive tests are the first methods for diagnosing Helicobacter pylori (HP) infection. Among these, serological test, stool antigen research and urea breath test are the most used. Antibodies anti-HP are not recommended in low prevalence population, moreover they cannot reveal an ongoing infection, but they only prove a contact with the bacterium. Also, they can persist for a long time after the eradication of the infection, therefore, they should not be used to verify the success of eradication therapy. Stool antigen research and Urea Breath Test (UBT) are useful both in diagnosis and during follow-up after eradication treatment. The stool antigen test is cheaper than Urea breath test with similar sensitivity and specificity.  Non-invasive tests are not able to diagnose the associated complications to HP infection.